(3GdNejS aj CMhGd CfaS fajSs - (3MSjf Hf eMeO Hf GdMSf GdOjGQ HcQj,J (B966 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ndb JhQ fHjg bHd cd ChGFd s
(3BNQgG (B:s
(3haQZ efg eDdag MSjf Hf eMeO Hf GdMSf GdOjGQ HcQi ai UZQ SfI NeS hKdGKjf hJSYeGFI HecI GdeTQaI s
(3QJHg GdeDda Ydi ebOeI hKdGKI CQcGf hNGJeIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B256 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B47s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B381 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B126 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B725s
Keywords: (3GdJGQjNs